2013
DOI: 10.3354/meps10069
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase activity detected in distinct phytoplankton communities in the northern Gulf of Alaska

Abstract: Alkaline phosphatase activity (APA) has been proposed as a proxy to determine phosphorus (P) stress in marine phytoplankton. Phytoplankton typically meet P requirements by incorporating dissolved inorganic P (DIP), but can use reservoirs of dissolved organic P (DOP) by expressing alkaline phosphatase (AP). Enzyme-labeled fluorescence (ELF) was used to determine group-specific APA within 4 phytoplankton communities associated with mesoscale eddies, which are common to the northern Gulf of Alaska (nGoA). Nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…The average APA in the G5 group was 0.0095 mmol·L −1 ·h −1 , which was significantly higher than that in other groups. This indicated that M. aeruginosa could utilize macromolecule organic P by releasing alkaline phosphatase, but alkaline phosphatase had no effect on small molecule organic P and inorganic P. This conclusion was similar to that in related studies [50].…”
Section: Discussionsupporting
confidence: 89%
“…The average APA in the G5 group was 0.0095 mmol·L −1 ·h −1 , which was significantly higher than that in other groups. This indicated that M. aeruginosa could utilize macromolecule organic P by releasing alkaline phosphatase, but alkaline phosphatase had no effect on small molecule organic P and inorganic P. This conclusion was similar to that in related studies [50].…”
Section: Discussionsupporting
confidence: 89%
“…It is expected that different taxa would present diverse strategies for coping with P limitation, but even among the dinoflagellates, it is likely that there will be species with different physiological P status, despite being exposed to identical ambient concentrations of P i and DOP (Mackey et al, 2007(Mackey et al, , 2012Peacock and Kudela, 2013). Indeed, our bioassay reveals that even at the highest Pi concentrations some dinoflagellate species presented ELF.…”
Section: Species-specific P Nutrition Sourcesmentioning
confidence: 75%